Organizational Supports and Organizational Deviance: The Mediating Role of Organization-Based Self-Esteem - FERRIS, Donald L. (Institutional Knowledge at Singapore Management University, 2009)
Drawing upon belongingness theory, we tested organization-based self-esteem (OBSE) as a mediator of the relation between organizational supports and organizational deviance. Data from 237 employees were collected at three points in time over one year. Using structural equation modeling, we found that OBSE fully mediated the relation between organizational supports and organizational deviance. Controlling for preexisting predictors of deviance, including personality traits (agreeableness, neuroticism and conscientiousness) and role stressors (role conflict, ambiguity, and overload), did not eliminate the relation between OBSE and organizational deviance. The implications for the OBSE and deviance literatures are discussed.